Women in Doubt: Women's Representation in K-Drama Series Search: WWW - Tarisha Artya Andjani; Firly Annisa (Jogjakarta Communication Conference (JCC), 2024)
Korean film and drama serve as powerful mediums of mass communication, capable of portraying and depicting the realities inherent in the cultural and social fabric of Korean society. "Search: WWW," a Korean drama released in 2019, delves into the conflicts, triumphs, and setbacks experienced by its female protagonists in the workplace. This study aims to examine the portrayal and representation of women in "Search: WWW." Employing a constructivist paradigm with a qualitative approach, the author seeks to identify and analyze signs of patriarchal culture manifested in the female characters using Roland Barthes' semiotic analysis method, encompassing denotation, connotation, and myth. The findings of this research underscore the significant role of media in shaping the perception of women in "Search: WWW." Despite featuring female characters with successful careers, characterized by self-reliance, intelligence, rationality, and determination, the study reveals underlying narratives cautioning women against certain pursuits, such as prioritizing independence and solitude, seeking divorce for freedom, and acquiescing to figures of greater power. Thus, the drama continues to reflect the patriarchal norms prevalent in Korean society.